Center of Group is Subgroup

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $G$ be a group.

The center $\map Z G$ of $G$ is a subgroup of $G$.


Proof 1

For brevity, suppress the symbol for the group operation (which may be $\circ$, or $+$).

Apply the Two-Step Subgroup Test:


Condition $(1)$

By the definition of identity, $e g = g e = g$ for all $g \in G$.

So, $e \in \map Z G$, meaning $\map Z G$ is non-empty.

$\Box$


Condition $(2)$

Suppose $a, b \in \map Z G$.

Using the associative property and the definition of center, we have:

$\forall g \in G: \paren {a b} g = a \paren {b g} = a \paren {g b} = \paren {a g} b = \paren {g a} b = g \paren {a b}$

Thus, $a b \in \map Z G$.

$\Box$


Condition $(3)$

Suppose $c \in \map Z G$. Then:

\(\displaystyle c\) \(\in\) \(\displaystyle \map Z G\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \forall g \in G: c g\) \(=\) \(\displaystyle g c\) Definition of center
\(\displaystyle \leadsto \ \ \) \(\displaystyle c^{-1} \paren {c g} c^{-1}\) \(=\) \(\displaystyle c^{-1} \paren {g c} c^{-1}\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \paren {c^{-1} c} g c^{-1}\) \(=\) \(\displaystyle c^{-1} g \paren {c c^{-1} }\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle e g c^{-1}\) \(=\) \(\displaystyle c^{-1} g e\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle g c^{-1}\) \(=\) \(\displaystyle c^{-1} g\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle c^{-1}\) \(\in\) \(\displaystyle \map Z G\)

$\Box$


Therefore:

$\map Z G \le G$

$\blacksquare$


Proof 2

We have the result Center is Intersection of Centralizers.

That is, $\map Z G$ is the intersection of all the centralizers of $G$.

All of these are subgroups of $G$ by Centralizer of Group Element is Subgroup.

Thus from Intersection of Subgroups is Subgroup, $\map Z G$ is also a subgroup of $G$.

$\blacksquare$


Sources